Computational Science and Technology 4th ICCST 2017, Kuala Lumpur, Malaysia, 29-30 November, 2017 (Lecture Notes in Electrical Engineering,, 2018)
This book gathers the proceedings of the Fourth International Conference on Computational Science and Technology 2017 (ICCST2017), held in Kuala Lumpur, Malaysia, on 29-30 November 2017. These proceedings offer practitioners and researchers the opportunity to present exciting advances in computational techniques and solutions in this area. They also identify emerging issues, help to shape future research directions, and will enable industrial users to apply cutting-edge, large-scale and high-performance computational methods.